Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Pemahaman Konsep Fisika di MIS Tabiyatul Athfal, Ciomas, Bogor Jawa Barat - Nurlaela, Siti; Rosadah, Siti; Hadi, Sopian (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Physics learning in Madrasah Ibtidaiyah (MI) often faces challenges because it is abstract and difficult for students to understand. At MIS Tabiyatul Athfal, many students have difficulty in understanding the relationship between Physics concepts and the phenomena around them. One of the causes is conventional learning methods that do not involve students actively. To overcome this, the Discovery Learning model is applied as an innovative approach that encourages independent exploration and discovery of concepts. This study aims to analyze the effectiveness of the Discovery Learning model in improving the understanding of Physics concepts of grade V students of MIS Tabiyatul Athfal. The method used was Classroom Action Research (PTK) with two cycles involving planning, implementation, observation, and reflection. Data were collected through observation, interviews, and concept understanding tests before and after the application of the model. The results showed that the Discovery Learning model significantly improved students' understanding of Physics concepts, critical thinking skills, and learning motivation. Students became more active in exploration, more able to connect theory with real phenomena, and more confident in conveying their understanding. Thus, this model is recommended as an effective learning strategy in learning Physics in MI